Children's Early Decontextualized Talk Predicts Academic Language Proficiency in Midadolescence. Issue 5 (23rd January 2018) - Uccelli, Paola; Demir‐Lira, Özlem Ece; Rowe, Meredith L.; Levine, Susan; Goldin‐Meadow, Susan
Abstract : This study examines whether children's decontextualized talk—talk about nonpresent events, explanations, or pretend—at 30 months predicts seventh‐grade academic language proficiency (age 12). Academic language (AL) refers to the language of school texts. AL proficiency has been identified as an important predictor of adolescent text comprehension. Yet research on precursors to AL proficiency is scarce. Child decontextualized talk is known to be a predictor of early discourse development, but its relation to later language outcomes remains unclear. Forty‐two children and their caregivers participated in this study. The proportion of child talk that was decontextualized emerged as a significant predictor of seventh‐grade AL proficiency, even after controlling for socioeconomic status, parent decontextualized talk, child total words, child vocabulary, and child syntactic comprehension.